High genomic connectivity within Anatoma at hydrothermal vents along the Central and Southeast Indian Ridge - Katharina Kniesz; Leon Hoffman; Pedro Martínez Arbizu; Terue C. Kihara (Scientific Reports)
Abstract Hydrothermal vents are ecosystems inhabited by a highly specialized fauna. To date, more than 30 gastropod species have been recorded from vent fields along the Central and Southeast Indian Ridge and all of them are assumed to be vent-endemic. During the INDEX project, 701 representatives of the genus Anatoma (Mollusca: Vetigastropoda) were sampled from six abyssal hydrothermal vent fields. Traditional morphology and COI barcoding of Hoffman et al. (Eur J Taxon 826:135–162, 2022) were combined with 2b-RAD sequencing to investigate the anatomid community structure and connectivity between the different vent fields. Consequently, 2b-RAD sequencing supported the primary species hypothesis (based on morphology) for 125 individuals of the recently described taxa A. discapex, A. declivis, A. laevapex and A. paucisculpta. We assigned 22 additional specimens to species with 2b-RAD sequencing and updated the community analyses that confirmed the pattern of expanding populations. Population structure and FST values indicated high connectivity along the six sampled vent fields for the three most abundant species. High levels of gene flow are suggested, pointing to high dispersal potential of the target species along the study area. However, low levels of heterozygosity revealed a small gene pool and therefore an increased vulnerability towards environmental change. Our results demonstrate that 2b-RAD sequencing, in combination with other molecular methods, can accurately characterise macrobenthic mollusc communities. Sequencing technology is an essential tool for ongoing monitoring. Furthermore, we highlight that the inferred molecular and ecological patterns provide valuable insights into hydrothermal vent ecosystems, which are crucial for the successful conservation of these ecosystems.